Efficacy of Some Plant Based and Conventional Chemical Insecticides to Control the Dubas Bug Ommatissus lybicus De Berg (Homoptera: Tropiduchidae). - الربيعي, حسين فاضل; خلف, محمد زيدان; محمد, طه موسى; حمود, جواد بلبل; نهر, فلاح حنش (Journal of Kerbala for Agricultural Sciences, 2015)
Field experiments were conducted to evaluate the efficacy of some plant based and conventional chemical insecticides as EC and ULV against second and third instar nymph of Ommatissus lybicus on date palms during spring and autumn generation of 2013 and 2014, respectively. The results showed that most of botanical insecticides used had very high efficacies, with relatively similar to that of conventional ones. In most trials, the average number of nymphs / leaflet reduced significantly,0.2 – 6.3 nymphs per leaflet compared with 20.2 in control treatment which showed continuous increase in number of nymph on the leaflet. Consequently , the percentage of pesticides efficacies obviously increased in most treatments 60 – 95%, particularly after seven days. Therefore, plant based insecticides could be considered as a successful alternative aspect to the conventional insecticides in management and control program of dubas bug.